VARIETIES OF ENGLISH AND THEIR SOCIAL CONTEXT - Yakubova, Madina (Журнал иностранных языков и лингвистики, 2021)
The article devoted to the varieties of English Language and their social context. The notion of “English languages” was analyzed as well as ideas of famous linguists as B. Kachru, R. Kirk were presented. The author brought the evidence that English is owned not only by native speakers, but also by the people who learn it.